Notas discursivas sobre autoria na rede (WEB) : o funcionamento polifônico da autoria no sistema computacional NELL - Hruschka, Estevam Rafael (Universidade Federal de São Carlos, 2016)
This research work aims at giving thought to the authorship concept when applied to a computational system – NELL (Never-Ending Language Learner) - that was designed to read the WEB in order to automatically build a consistent knowledge repository to be digitally stored. The internet is the primary input source for the system, and using a so called “neverending” reading process, the computer program is capable of accessing and fetching the whole internet content. Following the idea of exploring the relations and interactions among concepts, contexts and facts stated over the internet, the computer system will generate its own knowledge base, which will allow it to immediately answer questions on any domain. Considering the promising initial results obtained so far, studying and investigating theoretical approaches proposed by researchers from de authorship over de internet, having NELL as co-reference, is the main goal of the scientific research described in this document. This work is guided, basically, by the theoretical presupposition, as well as by the position and opinion of the following researchers: Michel Foucault, in its work: “O que é um Autor?”; Dominique Maingueneau: “Doze Conceitos em Análise do Discurso”, “Cenas da Enunciação” and “Discurso Literário”; Sírio Possenti: “Indícios de Autoria”; the Roger Chartier approach based on Michel Foucault work “O que é um Autor? Revisão de uma genealogia”; and Eni P. Orlandi: Interpretação; Autoria, leitura e efeitos do trabalho simbólico. Which are works that explore the target research topic. Based on the performed studies and analyses, our initial conclusions reveal that NELL’s authorship happens as in a polyphonic game of different voices.
Keywords: Discurso; Autoria; Speech; Authorship; NELL; Internet; LINGUISTICA, LETRAS E ARTES::LINGUISTICA